IN-PATIENT OUTCOMES OF PHARMACOINVASIVE REPERFUSION STRATEGY FOR ST ELEVATION MYOCARDIAL INFARCTION - A. V. Khripun; M. V. Malevanny; Ya. V. Kulikovskikh; A. A. Kastanyan (Российский кардиологический журнал, 2016)
Aim. To evaluate efficacy of pharmacoinvasive strategy (PCS) of treatment in ST elevation myocardial infarction (STEMI) in Rostovskaya Region, during the nearest (in-patient) period.Material and methods. The analysis performed, of 587 STEMI patients, who were referred to Regional Vascular Center “ROKB” of Rostov-na-Donu city from hospitals of the city and neighborhoods since January 2010 till June 2015, with the aim to undergo percutaneous coronary intervention (PCI) after thrombolytic therapy (TT) as PCS reperfusion strategy. Timeline mediana from pain onset to the start of TT was 140 minutes (interquartile range: 80,5-205 min). In 36,5% cases, TT was done at prehospital stage. Timeline mediana between TT and PCI was 34 hours. The results were evaluated in the nearest (in-hospital) period by the parameters as success of TT by ST dynamics on ECG, the level of blood flow restore in infarction-related artery (IRA) by TIMI score on coronary arteriography after TT in finishing of PCI, the rate of bleedings by TIMI and combinatory parameter of major adverse cardiovasular events (death, recurrent MI, stroke, need for another revascularization of target vessel).Results. ТТ regarded as successful in 52,5% of patients. By the results of coronary arteriography, blood flow TIMI-2/3 after TT was reached in 378 from 586 (64,5%) of patients. Stenting of coronary arteries was done in 548 among 586 (93,5%) of patients; in 25 (4,3%) of patients after TT there were no hemodynamically significant stenoses, in 13 (2,2%) patients stenting of IRA was technically impossible. Application of PCS in STEMI treatment made it to achieve TIMI-2/3 blood flow in IRA in 98,5% (577 among 586) patients. Rate of major bleedings was 1,9%. Stent thrombosis and recurrent infarctions did not happen, in-hospital mortality was 3,6%, rate of major adverse cardiovascular events — 3,7%.Conclusion. PCS makes it to increase time parameters of reperfusion and to increase its efficacy comparing to thrombolysis in those hospitals where it is impossible to perform primary PCI to improve long-term results of PCS it is important to reduce the time “pain-needle”, and to perform coronary angiography in maximum short time after thrombolysis. Regardless that the PCS matches with the region specifics, it is important to optimize healthcare with the aim to perform primary PCI for the highest possible number of patients.